The Constitutional Status of Islam in the Iraqi Legal Order - Khdir, Rebaz Rasul (Journal of Legal and Political Studies, 2024)
The region of Iraq has been part of the Islamic world since the dawn of Islamic Caliphate. Hence, Islam has played an essential role in the foundation and function of the country’s legal order until the downfall of the Ottoman Empire. Following the constitution of the new state of Iraq, Islam was incorporated as merely state religion and a civil right in the 1925 Constitution. This secular status remained in force until the republican era and the adoption of the 1964 Interim Constitution in which Islam was considered as the basic constitutional principle as well. Yet, the drafters of the 1970 Interim Constitution reformulated the relevant provision and rearticulated Islam as only state religion again. In 2003, the US-led Intervention resulted in the change of the political system in Iraq. The new regime incorporated Islam as a foundation source of legislation and a mirror principle in the 2005 Constitution which accordingly the law-making process must completely be based or conformable with the religion. However, the Iraqi legal order has been experiencing many incompatibilities of its legislative instruments with this constitutional principle as primarily the drafting processes of the laws mostly date back to the reign of the previous regimes, specifically when the status of Islam was a mere state religion and not a constitutional basis for the ordinary and subordinate legislation. Keyword: Islam, Iraqi legal order, constitution, ordinary legislation, constitutional supremacy.
Keywords: Islam; Iraqi legal order; constitution; ordinary legislation; constitutional supremacy